Special delivery: distributing iron in the cytosol of mammalian cells - Philpott, Caroline C.; Ryu, Moon-Suhn (Frontiers in Pharmacology, 2014)
Eukaryotic cells contain hundreds of proteins that require iron cofactors for activity. These iron enzymes are located in essentially every subcellular compartment; thus, iron cofactors must travel to every compartment in the cell. Iron cofactors exist in three basic forms: Heme, iron–sulfur clusters, and simple iron ions (also called non-heme iron). Iron ions taken up by the cell initially enter a kinetically labile, exchangeable pool that is referred to as the labile iron pool. The majority of the iron in this pool is delivered to mitochondria, where it is incorporated into heme and iron–sulfur clusters, as well as non-heme iron enzymes. These cofactors must then be distributed to nascent proteins in the mitochondria, cytosol, and membrane-bound organelles. Emerging evidence suggests that specific systems exist for the distribution of iron cofactors within the cell. These systems include membrane transporters, protein chaperones, specialized carriers, and small molecules. This review focuses on the distribution of iron ions in the cytosol and will highlight differences between the iron distribution systems of simple eukaryotes and mammalian cells.